Update on Biological Therapeutics for Asthma - Marisha L. Cook, MD; Bruce S. Bochner, MD (World Allergy Organization Journal, 2010)
Asthma poses a significant burden on patients, families, health care providers, and the medical system. While efforts to standardize care through guidelines have expanded, difficulty in managing severe asthma has encouraged research about its pathobiology and treatment options. Novel biologic therapeutics are being developed for the treatment of asthma and are of potential use for severe refractory asthma, especially where the increased cost of such agents is more likely justified. This review will summarize currently approved (omalizumab) and investigational biologic agents for asthma, such as antibodies, soluble receptors, and other protein-based antagonists, and highlight recent published data on efficacy and safety of these therapies in humans. As these newer agents with highly targeted pharmacology are tested in asthma, we are also poised to learn more about the role of cytokines and other molecules in the pathophysiology of asthma. Keywords: asthma, biologic therapies, cytokines, monoclonal antibodies